2013
DOI: 10.1080/15389588.2013.868893
|View full text |Cite
|
Sign up to set email alerts
|

Use of Illicit Drugs by Truck Drivers Arriving at Paranaguá Port Terminal, Brazil

Abstract: This research provides preliminary evidence that the use of illicit stimulants was common among professional truck drivers transporting grain loads. Thus, actions are needed to reduce drug use among truck drivers in order to prevent drug-related road traffic injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…11 Similarly, studies from Brazil have shown average driving hours that exceed the limits imposed by law, as well as high prevalence of sleepiness and use of amphetamines. 13,17,18 Limited evidence from limited countries shows nevertheless poor adherence to current provisions. In high-income countries, noncompliance to hours of service regulations has been also widely documented.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, studies from Brazil have shown average driving hours that exceed the limits imposed by law, as well as high prevalence of sleepiness and use of amphetamines. 13,17,18 Limited evidence from limited countries shows nevertheless poor adherence to current provisions. In high-income countries, noncompliance to hours of service regulations has been also widely documented.…”
Section: Discussionmentioning
confidence: 99%
“…Although hair analysis offers a large detection window for many substances, the positivity rate found was lower than that revealed by previous research in which oral fluid or urine samples were collected randomly from professional drivers on Brazilian roads. For instance, the positivity rates for cannabinoids, cocaine and amphetamines taken together varied from 5.2% using oral fluid to 8.1–9.3% in urine samples .…”
mentioning
confidence: 99%
“…According to the World Health Organization, Brazil ranks fifth in the world regarding deaths due to road crashes (approximately 40 000 deaths per year) . Recent researches have indicated that not only alcohol but also illicit drug use is a serious problem among Brazilian professional drivers . Efforts to create a specific offence of driving under the influence of drugs (DUID), together with drug tests, have been implemented recently in some countries, such as the United States, European countries and Australia .…”
mentioning
confidence: 99%